Primary Cutaneous Actinomycosis of Lower Extremity: A Rare Case Report (Anwer Khan Modern Medical College Journal, 2015)
Actinomycosis is a chronic, suppurative, and granulomatous process caused by actinomycetes, saprophytic bacteria normally residing in the oral cavity. There are a few cases of primary actinomycosis described in the literature where it can involve any organ. Primary cutaneous actinomycosis of the lower extremity is very uncommon and can easily be regarded as ordinary soft tissue infection. Herein, a case of 45-year-old diabetic man with primary cutaneous actinomycosis at his lower extremity, over the lateral aspect of left lateral maleolus, probably after direct inoculation of the microorganism from his saliva into a preceding wound in extremity, was reported. He was treated successfully with surgical excision combined with extended period of antimicrobial treatment.Anwer Khan Modern Medical College Journal Vol. 6, No. 1: January 2015, Pages 55-57